(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Background Nanotechnology is an exciting new field in science, with many possible applications in medicine. This article seeks to define the role of nanoparticles in medicine in terms of drug conduction, the applications of nanoscale and nanostructures are explained, as well as the classification of nanomaterials and methods of preparing nanoparticles in terms of applications of nanoparticles in drug delivery, and cancer. Conclusion: Also discussed the applications of various nanostructures in cancer treatment such as carbon nanotubes,